The road to entrepreneurial success: Business plans, lean startup, or both? - Chris Welter; Alex Scrimpshire; Dawn Tolonen; Eseoghene Obrimah (New England Journal of Entrepreneurship (NEJE), 2021)
Purpose The goal of this research is to investigate the relationship between two different sets of practices, lean startup and business planning, and their relation to entrepreneurial performance. Design/methodology/approach The authors collected data from 120 entrepreneurs across the US about a variety of new venture formation activities within the categories of lean startup or business planning. They use hierarchical regression to examine the relationship between these activities and new venture performance using both a subjective and objective measure of performance. Findings The results show that talking to customers, collecting preorders and pivoting based on customer feedback are lean startup activities correlated with performance; writing a business plan is the sole business planning activity correlated with performance. Research limitations/implications This research lays the foundation for understanding the components of both lean startup and business planning. Moreover, these results demonstrate that the separation of lean startup and business planning represents a false dichotomy. Practical implications These findings suggest that entrepreneurs should engage in some lean startup activities and still write a business plan. Originality/value This article offers the first quantitative, empirical comparison of lean startup activities and business planning. Furthermore, it provides support for the relationship between specific lean startup activities and firm performance.
Keywords: 650; Business planning; Entrepreneurship; Lean Startup